Association between genetic mutations in lung adenocarcinoma and adult body mass index: a retrospective cohort study - Wu, Yan qiao; Yang, Lei; Jiang, Depeng (Frontiers in Oncology, 2025)
BackgroundThe impact of obesity on gene mutations in lung adenocarcinoma(ADC) remains unclear. This study investigates the association between Body Mass Index(BMI) and the gene mutation in ADC.MethodsThis study investigated the relationship between BMI and ADC gene mutation. Logistic regression model was used to verify the association between BMI and ADC gene mutations. Threshold effect analysis is used to distinguish between linear and nonlinear. Subgroup analyses rigorously assessed demographic variations, significantly strengthening the study’s credibility. Concurrently, the ROC curves were utilized to predict ADC gene mutation.ResultsIn our study, average ages of 66.00 vs. 65.00 were observed for ADC with gene mutation and ADC without gene mutation, respectively. After adjusting for covariates, a significant negative association emerged between BMI and ADC gene mutation, revealing a linear association(OR = 0.820, 95% CI: 0.680-0.982, p = 0.030). ROC curve analysis demonstrated AUC values of 0.533(all BMI) and 0.625(Q2, 21.08 ≤ BMI < 22.86kg/m2) for predicting tumor gene mutation. Spearman’s analysis further indicated a negative correlation between tumor gene mutations and BMI(Q2, OR= -0.215, p = 0.032). Patients younger than 60 years of age, women and those without a history of smoking and drinking had a relatively high rate of ADC gene mutations.ConclusionThis study reveals a significant association between BMI and ADC gene mutations, demonstrating that elevated BMI levels correlate negatively with mutation risk within the specific range of 21.08 to 22.86 kg/m². Furthermore, the rate of gene mutation may be relatively high in women under the age of 60 who do not smoke or drink. This study may assist clinicians in preliminarily assessing the gene mutation status of patients with ADC.